Compreendendo a pessoa em experiência suicida a partir de um serviço de plantão psicológico centrado na pessoa - Alves, Felipe Rodrigues (2020)
Suicide, as a complex phenomenon, is responsible for death of thousands people, which needs to be understood based on many factors like personal, biological, psychiatric, psychological, sociocultural, religious and environmental aspects. This study intended to understand how can people experiement a situation of suicide from a Person-Centered Psychological Service offered in a context of a clinic school. A Suicidal experience is understood as ideations, plans, self-harm and suicide attempts. The theoretical foundation was built on the available theories about the topic and mainly about the foundations of the Person Centered Approach - which is the theoretical perspective developed by Carl Rogers. This research, characterized as qualitative approach, was carried out with 10 participants, 7 women and 3 men, mostly composed of university students, single, aged 18 to 24 years old. For the data analysis, a new model was proceeded using the Version's Meaning Method - implemented by Amatuzzi - and the Comprehensive Analysis Centered on Duty. In original, it consists in an expressive elaboration report as fast as possible while happens. However, in this case, we resumed the recordings on duty, listening audio tapes recorded during duty. It turned possible the construction of analysis categories about commom aspects narred by the participants. The ACCP was based on an attentive and sensitive reading of the transcripts, inspired on the procedures adopted by Rogers, allowing understanding and identifying the common and peculiar aspects of people who experience a situation of suicide. The procedures proved to be satisfactory. The results obtained through the ACCP allowed the identification of 43 common discursive elements, which were grouped into 10 categories of analysis - Need for positive self-consideration; The past that has not passed; Interpersonal variants; Ways to experience the suicidal experience; Personal conceptions; Emotional states; State of internal disagreement; Exits in the face of pain; Incentives to live and Need for help. The results set allowed us to conclue that the situation of suicidal experience lived by the participants is related to the appreciation of the affections shared with close people, mainly family members. The “other”, while facilitating the decision to kill oneself to be perceived, also acts as an important support for that person in life; the eminent intention expressed by the study's participants is to kill psychological pain and do not themselves as a person. There were also shared experiences of revitalizing the past, disconnection between the internal and external world, rigid personal conceptions, experiencing emotional states of loneliness, irritability, impatience, sensitivity, emotional fragility and anxiety; choice of ways out through self destruction, psychoactive substances and arts when faced with subjective pain and suffering; making significant efforts to maintain emotional strengthening; and the recognition of the need for help, suggesting self-care and value for life. The importance of creating public policies to these people is pointed out as an effective way to prevent self-destructive acts and health promotion, which the Person-Centered Psychological Service appears like one of these viable and promising possibilities.